Spiritual Camp Sebagai Model Pendidikan Toleransi di SMAN Kota Mataram - Abdurrohman Abdurrohman; Muh. Jaelani Al Pansori; Huldiya Syamsiar; Lalu M. Istiqlal (LPPM Institut Pendidikan Nusantara Global, 2026)
Studies on tolerance are not a new issue in multicultural societies; however, an examination of Spiritual Camp programs in schools that are specifically designed to foster inclusive and tolerant attitudes and behaviors among students is particularly interesting to investigate. This study aims to describe the implementation of Spiritual Camp activities as a model of tolerance education at SMAN 3 and SMAN 4 in the city of Mataram. The research employed a qualitative method with a case study approach conducted at SMAN 3 and SMAN 4 Mataram. Data were collected through observation, interviews, and document analysis. Data analysis utilized an interactive qualitative descriptive model, carried out through several stages, namely organizing and managing the data, data reduction, data interpretation, drawing conclusions, and verifying and validating the findings. The findings indicate that the Spiritual Camp program is effective in strengthening students’ faith and piety, fostering multicultural awareness, empathy, and a sense of brotherhood, as well as shaping inclusive and tolerant character traits among students. The implementation of Spiritual Camp activities at SMAN 3 and SMAN 4 Mataram encompasses religious activities that emphasize deepening religious knowledge and worship practices, as well as social and cultural arts activities. Each school demonstrates variations in both the content and the location of the activities, depending on the respective school policies. Despite these variations, all activities remain focused on the same core objectives, namely the strengthening of faith and piety and the formation of inclusive and tolerant student character. The implementation of the Spiritual Camp program has proven to be an effective model of tolerance education, as there have been no cases of intolerance, bullying, or violence reported in either of the two schools.